Pharmacogenomics of antihypertensive drugs: past, present and future - Johnson, Julie A (Pharmacogenomics, 2010)
Hypertension pharmacogenomics holds the promise of leading to individualized drug treatment approaches for the approximately 1 billion individuals worldwide with hypertension. Prior to 2000, the literature on hypertension pharmacogenomics was quite limited. The last decade has seen a substantial growth in the literature, with several examples of genes that appear to play an important role in antihypertensive response. The last decade has also made apparent the numerous challenges in hypertension pharmacogenomics, and addressing those challenges will be important. Moving forward, it seems clear that collaboration among researchers to allow replication or joint analyses will be essential in advancing the field, as will the use of genome-wide association approaches. The next decade should clearly define the clinical potential for hypertension pharmacogenomics.